2016
DOI: 10.1213/ane.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Combined with General Anesthesia Provides Similar Intraoperative Stress Response Reduction When Compared with a Combined General and Epidural Anesthetic Technique

Abstract: When used in conjunction with TIVA, intraoperative dexmedetomidine blunts surgical stress responses to an extent comparable to combined epidural and general anesthesia without compromising hemodynamic stability and with minimal adverse effects during the intraoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 54 publications
6
69
3
Order By: Relevance
“…21 The other study compared a dexmedetomidine infusion group with two other groups (epidural and control, n = 30 each group) during a gastrectomy and showed that dexmedetomidine decreased emergence agitation compared with the control (7% vs 27%). 22 Our result is in line with these previous studies. According to our distribution graph of Riker scales, most patients were scale 4 (calm, 41/60, 68.3%) in the DEX-Sevo group.…”
Section: Discussionsupporting
confidence: 94%
“…21 The other study compared a dexmedetomidine infusion group with two other groups (epidural and control, n = 30 each group) during a gastrectomy and showed that dexmedetomidine decreased emergence agitation compared with the control (7% vs 27%). 22 Our result is in line with these previous studies. According to our distribution graph of Riker scales, most patients were scale 4 (calm, 41/60, 68.3%) in the DEX-Sevo group.…”
Section: Discussionsupporting
confidence: 94%
“…Dexmedetomidine can be used as an adjuvant in the perioperative setting. When administered during surgery, dexmedetomidine reduces the consumption of opioids and anaesthetics, and blunts the stress response via reduced levels of serum catecholamines, cortisol and cytokines. Intraoperative dexmedetomidine has been shown to reduce the incidence of delirium in children.…”
Section: Introductionmentioning
confidence: 99%
“…NE, E, Cor, tumor necrosis factor-α and IL-6 compared with combined general and epidural anesthesia. What's more, the former obtained hemodynamic stability and less adverse effects during the surgery [27]. As a preanesthetic medication (1 μg/kg) and intraoperative infusion (0.5 μg/kg/h), DEX was found to be effective in suppressing metabolic stress response to major abdominal surgeries as indicated by stable blood glucose levels [28].…”
Section: Discussionmentioning
confidence: 96%